Implementasi Kebijakan Untuk Menekan Peredaran Rokok Ilegal Di Kantor Pengawasan dan Pelayanan Bea dan Cukai B Pekanbaru - Juniardi, Kristanto (Universitas Sang Bumi Ruwa Jurai, 2025)
This study aims to explore how supervisory and enforcement policies are implemented by the Customs and Excise Office of Type Madya Pabean B Pekanbaru in the context of enforcing customs regulations, while also identifying various obstacles encountered during the implementation process. The methodology employed in this research adopts a qualitative approach combined with a descriptive research model. The data were collected primarily through direct field observation and in-depth interviews. The data analysis process involved several stages: data collection, data reduction, structured data presentation, and finally, drawing conclusions based on empirical findings. The results of this study indicate that the policies implemented are in accordance with the prevailing legal provisions. However, several challenges persist, particularly regarding the availability and capacity of human resources, limitations in infrastructure and facilities, and weak inter-agency coordination. Therefore, improvement strategies should focus on enhancing cross-institutional collaboration and ensuring consistent law enforcement to create a deterrent effect for violators of excise regulations